On Some Founding Ideas of Quailology and Their Propounders - Fred S. Guthery (National Quail Symposium Proceedings, 2017)
Powerful ideas in quailology affect thinking over generations, even if the ideas are wrong. I discuss great ideas put forth by Aldo Leopold, Herbert Lee Stoddard, and Paul Lester Errington and comment on aspects of their personalities. Leopold, an extraordinarily good father, posited the Law of Dispersion (Interspersion), which became known as the Principle of Edge. The Law is a tautology that can be paraphrased ‘edge-obligate animals require edge.’ Leopold observed the ‘law’ held ‘within ordinary limits,’ which he did not define but which could mean ‘within compositionally simple landscapes.’ As a child, Stoddard, who dropped out of high school to support his family, recognized the value of fire in northern bobwhite (Colinus virginianus) habitat management in the Southeast; later he came to see tenant farming (patchwork agriculture) set up conditions favorable to northern bobwhites. Stoddard was given to after- the-fact hypothesis formulation (retroduction) on the causes of events he observed. Through this logically weak process he bequeathed many ‘facts’ that are really untested hypotheses. Errington, an apparent loner who survived polio as a child, had 2 great ideas. The Threshold of Security was a fairly constant spring density which implied harvest up to a certain level is fully compensatory (doomed- surplus model). The Principle of Inversity implies that relative productivity declines as breeding density increases. Errington’s own work refuted the doomed-surplus model because he could not have simultaneously observed a constant breeding population and inversity, which requires a variable breeding population. These great founding ideas, although not without flaw, arose through observation of nature and thought, not through null hypothesis significance testing and model selection.
Keywords: Colinus virginianus; Errington; Leopold; northern bobwhite; stoddard